Recombinant human diamine oxidase prevents histamine-induced hypoxia, shock and death in guinea pigs - Felix Kosta; Matthias Weiss-Tessbach; Elisabeth Gludovacz; Birgit Reiter; Martin Murauer; Bernd Jilma; Marlene Rager-Resch (Inflammation Research, 2026)
Background and objective Histamine is the principal effector of anaphylaxis, and circulating levels correlate well with symptom severity in Hymenoptera venom–induced anaphylaxis. Adrenaline, the recommended first-line therapy, does not neutralize histamine and may cause relevant adverse effects. Recombinant human diamine oxidase (rhDAO), engineered with a mutated heparin-binding motif, exhibits improved pharmacokinetics and rapid histamine-degrading activity. The primary aim of this study was to evaluate whether prophylactic or particularly therapeutic rhDAO prevents or reduces histamine-induced shock compared with adrenaline in guinea pigs. Methods Guinea pigs received subcutaneous histamine (1 mg/kg) with or without intramuscular adrenaline or intravenous rhDAO (2–8 mg/kg). Mean arterial pressure, heart rate, and arterial oxygen partial pressure (PaO₂) were monitored. Plasma histamine and rhDAO levels were measured. Results Histamine injection raised plasma levels above 200 ng/ml and consistently induced shock with 42% mortality. Prophylactic and therapeutic rhDAO completely degraded circulating histamine, reduced shock incidence from 100% to 0% at the highest doses, shortened tachycardia, improved PaO₂ and decreased mortality. Intramuscular adrenaline (0.005 or 0.01 mg/kg) did not improve hemodynamics, oxygenation or survival. Conclusion Recombinant hDAO prevented and treated histamine-induced shock and hypoxia, whereas adrenaline was ineffective. These findings support clinical development of rhDAO for life-threatening histamine-mediated conditions, including anaphylaxis.

The power of trapped ion mobility for isotope tracer experiments - Karin Preindl; Chuqiao Chen; Supriya Murthy; Florian Gruber; Christian Freystätter; Thomas Weichhart; Thomas Stimpfl; Birgit Reiter; Arvand Haschemi; Gunda Koellensperger (Analytica Chimica Acta, 2025)

Mass spectrometry-based analysis of eccrine sweat supports predictive, preventive and personalised medicine in a cohort of breast cancer patients in Austria - Michael Bolliger; Daniel Wasinger; Julia Brunmair; Gerhard Hagn; Michael Wolf; Karin Preindl; Birgit Reiter; Andrea Bileck; Christopher Gerner; Florian Fitzal; Samuel M. Meier-Menches (EPMA Journal, 2025)
Objective Metabolomics measurements of eccrine sweat may provide novel and relevant biomedical information to support predictive, preventive and personalised medicine (3PM). However, only limited data is available regarding metabolic alterations accompanying chemotherapy of breast cancer patients related to residual cancer burden (RCB) or therapy response. Here, we have applied Metabo-Tip, a non-invasive metabolomics assay based on the analysis of eccrine sweat from the fingertips, to investigate the feasibility of such an approach, especially with respect to drug monitoring, assessing lifestyle parameters and stratification of breast cancer patients. Methods Eccrine sweat samples were collected from breast cancer patients ( n = 9) during the first cycle of neoadjuvant chemotherapy at four time points in this proof-of-concept study at a Tertiary University Hospital. Metabolites in eccrine sweat were analysed using mass spectrometry. Blood plasma samples from the same timepoints were also collected and analysed using a validated targeted metabolomics kit, in addition to proteomics and fatty acids/oxylipin analysis. Results A total of 247 exogenous small molecules and endogenous metabolites were identified in eccrine sweat of the breast cancer patients. Cyclophosphamide and ondansetron were successfully detected and monitored in eccrine sweat of individual patients and accurately reflected the administration schedule. The non-essential amino acids asparagine, serine and proline, as well as ornithine were significantly regulated in eccrine sweat and blood plasma over the therapy cycle. However, their distinct time-dependent profiles indicated compartment-specific distributions. Indeed, the metabolite composition of eccrine sweat seems to largely resemble the composition of the interstitial fluid. Plasma proteins and fatty acids/oxylipins were not affected by the first treatment cycle. Individual smoking habit was revealed by the simultaneous detection of nicotine and its primary metabolite cotinine in eccrine sweat. Stratification according to RCB revealed pronounced differences in the metabolic composition of eccrine sweat in these patients at baseline, e.g., essential amino acids, possibly due to the systemic contribution of breast cancer and its impact on metabolic turnover. Conclusion Mass spectrometry-based analysis of metabolites from eccrine sweat of breast cancer patients successfully qualified lifestyle parameters for risk assessment and allowed us to monitor drug treatment and systemic response to therapy. Moreover, eccrine sweat revealed a potentially predictive metabolic pattern stratifying patients by the extent of the metabolic activity of breast cancer tissue at baseline. Eccrine sweat is derived from the otherwise hardly accessible interstitial fluid and, thus, opens up a new dimension for biomonitoring of breast cancer in secondary and tertiary care. The simple sample collection without the need for trained personnel could also enable decentralised long-term biomonitoring to assess stable disease or disease progression. Eccrine sweat analysis may indeed significantly advance 3PM for the benefit of breast cancer patients.

Recombinant human diamine oxidase prevents hemodynamic effects of continuous histamine infusion in guinea pigs - Matthias Weiss-Tessbach; Birgit Reiter; Elisabeth Gludovacz; Thomas Boehm; Bernd Jilma; Marlene Rager-Resch (Inflammation Research, 2023)
Objective To test whether recombinant human diamine oxidase (rhDAO) with a mutated heparin-binding motif (mHBM), which shows an increased alpha-distribution half-life, prevents histamine-induced hemodynamic effects. Material Thirty-eight female guinea pigs were either pretreated with rhDOA_mHBM or buffer. Treatment and methods Guinea pigs received a continuous infusion of histamine. Heart rate (HR), body core temperature and mean arterial pressure (MAP) were measured and blood was collected. Results Continuous intravenous infusion of 8 µg/kg/min histamine increased mean peak plasma histamine levels from 5 (± 0.3 SEM) to 28 ng/mL (± 4.9 SEM) after 30 min but had no effect on oxygen saturation. Guinea pigs pretreated with 4 mg/kg rhDAO_mHBM showed lower mean HR ( p = 0.008), histamine plasma concentrations ( p = 0.002), and higher body core temperatures at the end of the histamine challenge ( p = 0.02) compared to controls. Cessation of histamine infusion led to a rebound increase in MAP, but this hemodynamic instability was prevented by rhDAO_mHBM. Pretreatment with 4 mg/kg rhDAO_mHBM reduced urinary histamine ( p = 0.004) and 1-Methylhistamine ( p < 0.0001) concentrations compared to controls. Conclusions Prophylactic infusion of rhDAO_mHBM prevents hemodynamic effects in a guinea pig model of continuous histamine infusion. These findings might help in the translation from animals to humans and in the selection of the optimal dosing of rhDAO_mHBM during human histamine challenge studies.

Impact of thrombocytes, on bacterial growth and antimicrobial activity of selected antibiotics - Alina Karoline Nussbaumer-Pröll; Sabine Eberl; Birgit Reiter; Thomas Stimpfl; Walter Jäger; Stefan Poschner; Markus Zeitlinger (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
In vitro pharmacodynamic models are used to optimize in vivo dosing regimens in antimicrobial drug development. One limiting factor of such models is the lack of host factors such as corpuscular blood components as erythrocytes which have already been shown to impact activity of antibiotics and/or growth of the pathogen. However, the impact of thrombocytes has not previously been investigated. We set out to investigate if the addition of thrombocytes (set to physiological concentrations in blood of healthy human, i.e., 5 × 10 5 thrombocytes/μL standard growth media Mueller Hinton Broth, MHB) has an influence on bacterial growth and on the efficacy of antibiotics against Gram+ and Gram− bacteria. Growth assays and time-killing-curves (TKC) were performed with ATCC-strains of Escherichia coli , Staphylococcus aureus , and Pseudomonas aeruginosa in triplicate over 24 h. The same approach was followed for 5 clinical isolates of Escherichia coli . Meropenem, ciprofloxacin, and tigecycline were tested as representatives of broad-spectrum antibiotics, and concentrations several-fold above and below the minimal inhibitory concentration (MIC) were simulated. No significant impact of thrombocytes was found on bacterial growth or antimicrobial stability for the investigated agents. Bacteria reduced thrombocyte content to different degree, indicating direct interaction of pathogens and thrombocytes. Impact on bacterial killing was observed but was not fully reproducible when thrombocytes from different donors where used. While interaction of bacteria and thrombocytes was evident in the present study, interaction between antibiotic activity and thrombocytes seems unlikely. Whether variability was caused by different thrombocyte concentrates needs further investigation.

Impact of erythrocytes on bacterial growth and antimicrobial activity of selected antibiotics - Alina Karoline Nussbaumer-Pröll; Sophie Knotzer; Sabine Eberl; Birgit Reiter; Thomas Stimpfl; Walter Jäger; Stefan Poschner; Markus Zeitlinger (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Endophytic Pseudomonasspp. populations of pathogen-infected potato plants analysed by 16S rDNA- and 16S rRNA-based denaturating gradient gel electrophoresis - Birgit Reiter; Nicola Wermbter; Stephen Gyamfi; Helmut Schwab; Angela Sessitsch (Plant and Soil, 2003)